Analytical Solution for Bending Steel Concrete Composite Plates considering the Shear Deformation Effect - Tien, Dao Ngoc; Tung, Nguyen Xuan; Lam, Nguyen Ngoc (Engineering, Technology & Applied Science Research, 2024)
This paper deals with an analytical approach to the static behavior of Steel Concrete Composite (SCC) slabs. The Classical Plate Theory (CPT) and Refined Plate Theory (RPT) are considered when constructing governing equations describing the behavior of steel concrete plates. The displacement fields are represented by trigonometric series to find the exact solution by applying Navier’s approach. Various numerical examples have been compared with the considered ones showing their high accuracy. The influence of plate parameters such as the thickness of steel and concrete layers on displacement was investigated in detail.